2021
DOI: 10.1016/j.adolescence.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Differences between male and female university students in sleepiness, weekday sleep loss, and weekend sleep duration

Abstract: Introduction: Women and men experience sleep differently and the difference in intrinsic desire for sleep might underlie some of the observed male-female differences. The objective of this crosssectional questionnaire study of university students was to determine male-female differences in self-reported sleepiness and sleep-wake patterns. Methods: Five questionnaires were completed by 1650 students at four Russian universities. Results: Compared to male students, female students reported a lower subjective sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
1
12
1
3
Order By: Relevance
“…Therefore, caffeine intake could modify the common circadian rhythm of melatonin, leading to sleep disturbances. Previous studies also reported worse values for different parameters related to sleep quality in female than in male students [16,17]. This is similar to the findings of the present study, showing worse subjective sleep quality in women.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, caffeine intake could modify the common circadian rhythm of melatonin, leading to sleep disturbances. Previous studies also reported worse values for different parameters related to sleep quality in female than in male students [16,17]. This is similar to the findings of the present study, showing worse subjective sleep quality in women.…”
Section: Discussionsupporting
confidence: 92%
“…However, most of the studies examined the association of subjective sleep quality with prevalence of caffeine sources' consumption rather than with the overall daily caffeine consumption as a continuous variable. In addition, the influence of sex should be considered when determinants of subjective sleep quality are analyzed because a poorer subjective sleep quality in women than in men has been commonly found, at least among university students [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The number of published samples was not big enough to perform multiple tests of the model’s prediction, and to confirm this result by several separate examinations for subsets of data representing two genders and several distinct age groups. Although the difference in intrinsic desire for sleep might underlie some of the observed male–female differences in sleep duration [ 27 ], much of the gap between men and women was explained by gendered time tradeoffs and by work and family responsibilities [ 28 ]. This gender gap might be further increased in the condition of “lockdown” in some of age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Being strongly affected by social factors and daily schedules, both sleep and PA patterns may vary as a function of their timing within the week. Previous work has demonstrated delayed sleep timing and increased sleep duration on free days compared to workdays (15,(18)(19)(20). PA patterns have also been shown to vary throughout the week, with some individuals demonstrating a "weekend warrior" pattern, in which most or all of weekly PA is performed on weekends (21).…”
Section: Introductionmentioning
confidence: 99%